PENGARUH PEMBERIAN TES KECIL (KUIS) DI AKHIR PEMBELAJARAN TERHADAP HASIL BELAJAR IPS - MULZA - ROIS; RIDHA MAHAYENI (LPPM Universitas Muhammadiyah Muara Bungo, 2019)
This research aims to determine the extent of the effect of giving a small test (quiz) at the end of learning on the results of social studies learning of the eighth grade students of MTsN Kubang Putih in the 2015/2016 academic year. This type of research is a Quasi Experiment study. The population in this study were all students of class VIII MTsN Kubang Putih totaling 6 classes. The sample in the study was determined by Random Sampling technique, selected class VIII.5 as the experimental class and class VIII.4 as the control class. The hypothesis in this study is that there is a significant effect between giving a small test (quiz) at the end of learning on the results of social studies learning of the eighth grade students of MTsN Kubang Putih. The data analysis technique used is by t test provided that the data must be normal and homogeneous, then the criteria will be accepted H_1 if t_count> t table is dk = n1 + n2 - 2 and α = 0.05. The results of data analysis obtained t_count = 3.32 and table with significant levels α = 0.05 is 1.68 and dk = n1 + n2 - 2. So t_count> t table. The conclusion of this study is that there is an influence of students' social studies learning outcomes by giving a small test (quiz) at the end of learning significantly higher. So the hypothesis is accepted at 95% confidence level.